The Role of Transaction Security Perception in Reducing the Risk of Churn for E-Wallet Users in Indonesia - Ahmad Lukman Nugraha (Journal of Digital Business and Data Science, 2025)
The development of e-wallet services in Indonesia shows rapid growth, but the high competition between players and the increase in digital crime cases pose a significant potential for churn. This study aims to analyze the influence of transaction security perception on the risk of churn in e-wallet users in Indonesia. The research method used a quantitative approach with a survey technique of 428 respondents who actively used e-wallet services. Data analysis was carried out through validity, reliability, and simple linear regression tests. The results showed that the perception of transaction security had a negative and significant effect on churn risk, with a regression coefficient value of -0.649 and a significance of <0.001. These findings confirm that the higher the perceived perception of security by users, the lower their tendency to move to another platform. An R² value of 0.421 indicates that the perception of security is able to explain a substantial proportion of the variation in churn risk. The study also identified that other factors such as digital service quality, user experience, feature innovation, promotion, and company reputation also influence churn behavior. The implications of this study underscore the importance of improving system security, privacy policy transparency, user education, and a comprehensive retention strategy in maintaining the loyalty of e-wallet users amid increasingly fierce industry competition.